Thermal performance analysis of a Solar parabolic dish concentrator system with modified cavity receiver. (4th January 2021) - Kumar, Varinder; Bopche, Santosh
Abstract : Purpose: This paper aims to present the numerical models and experimental outcomes pertain to the performance of the parabolic dish concentrator system with a modified cavity-type receiver (hemispherical-shaped). Design/methodology/approach: The numerical models were evolved based on two types of boundary conditions; isothermal receiver surface and non-isothermal receiver surface. For validation of the numerical models with experimental results, three statistical terms were used: mean of absolute deviation, R 2 and root mean square error. Findings: The thermal efficiency of the receiver values obtained using the numerical model with a non-isothermal receiver surface found agreeing well with experimental results. The numerical model with non-isothermal surface boundary condition exhibited more accurate results as compared to that with isothermal surface boundary condition. The receiver heat loss analysis based on the experimental outcomes is also carried out to estimate the contributions of various modes of heat transfer. The losses by radiation, convection and conduction contribute about 27.47%, 70.89% and 1.83%, in the total receiver loss, respectively. Practical implications: An empirical correlation based on experimental data is also presented to anticipate the effect of studied parameters on the receiver collection efficiency. The anticipations may help to adopt the technology for practical use. Social implications: The developed models would help to design and anticipating the performance of the dish concentrator system with a modified cavity receiver that may be used for applications e.g. power generation, water heating, air-conditioning, solar cooking, solar drying, energy storage, etc. Originality/value: The originality of this manuscript comprising presenting a differential-mathematical analysis/modeling of hemispherical shaped modified cavity receiver with non-uniform surface temperature boundary condition. It can estimate the variation of temperature of heat transfer fluid (water) along with the receiver height, by taking into account the receiver cavity losses by means of radiation and convection modes. The model also considers the radiative heat exchange among the internal ring-surface elements of the cavity.